Preparation method of hole transport layer, and preparation method and structure of solar cell

By mixing self-assembled molecular materials with metal oxide nanoparticles to form a single-layer hole transport layer and using a low-temperature annealing process, the problems of the hole transport layer in terms of environmental stability and preparation process complexity are solved, and the performance and stability of solar cells are significantly improved.

CN119907604APending Publication Date: 2025-04-29SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510094085.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, the hole transport layer has problems in environmental stability, production process complexity, high annealing temperature requirements and long-term stability, which affects the overall performance and long-term stability of solar cells.

Method used

By mixing a self-assembled molecular material including carbazole groups and phosphonic acid anchoring groups with metal oxide nanoparticles to form a single-layer hole transport layer and preparing by a low-temperature annealing process, the process flow is simplified and the environmental stability of the material is improved.

Benefits of technology

The high light transmittance and environmental stability of the hole transport layer are achieved, the preparation process is simplified, the annealing temperature requirements are reduced, and the photoelectric conversion efficiency and long-term performance of solar cells are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907604A_ABST
    Figure CN119907604A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a hole transport layer, a preparation method of a solar cell and a structure, and the method comprises the steps: carrying out the special processing of a self-assembly molecular material and metal oxide nanoparticles, and forming a single-layer hole transport layer which comprises the self-assembly molecular material and the metal oxide nanoparticles at the same time. The single-layer hole transport layer not only has high light transmittance, but also can effectively improve the environmental stability of the material in the hole transport layer, reduce the problem of degradation of the self-assembled molecular material and the metal oxide nanoparticle material caused by moisture and oxidation, and can effectively simplify the preparation process flow of the traditional multi-layer hole transport layer. And the process complexity is reduced. Besides, the single hole transport layer can effectively promote the improvement of the crystallization quality of the perovskite absorption layer while improving the transport efficiency, so that the crystallization is more uniform and compact, and the photoelectric conversion efficiency and the long-term performance of the solar cell are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells and relates to a method for preparing a hole transport layer, a method for preparing a solar cell and a structure thereof. Background Art

[0002] In recent years, perovskite solar cell technology has developed rapidly. As one of the key functional layers in the battery, the hole transport layer plays a vital role in improving the performance of the battery. At present, a common choice for high-performance hole transport layer materials is self-assembled molecular layers (SAMs). This type of material can form a good interface contact between the perovskite active layer and the electrode, improve the carrier transfer efficiency, and thus significantly improve the overall performance of the battery. In addition, due to its self-assembly characteristics, SAMs materials show excellent interface passivation effects in perovskite solar cells, which can effectively reduce interface defects and inhibit non-radiative recombination. However, although SAMs showed a better interface passivation effect in initial applications and effectively improved the interface properties between the perovskite layer and the electrode, its long-term stability is still insufficient. When exposed to environmental conditions (such as light, moisture, oxygen, etc.) for a long time, SAMs materials are prone to degradation, resulting in a weakening of the interface passivation effect. This phenomenon further weakens the interface bonding between the perovskite layer and the hole transport layer, thereby affecting the long-term performance of the battery. Therefore, how to improve the environmental stability of SAMs materials to ensure that their passivation effect does not diminish during long-term use has become one of the key challenges in technological development.

[0003] In order to solve this problem, an improved interface modification strategy has been proposed in recent years, that is, before preparing the SAMs hole transport layer, nickel oxide (NiO) nanoparticles are first introduced as the lower interface modification layer of the perovskite layer. Specifically, a layer of NiO nanoparticles is first deposited, and then a SAMs layer is prepared on it to form a stacked structure consisting of a NiO nanoparticle layer and SAMs. This structure can significantly enhance the interfacial bonding force between the perovskite layer and the hole transport layer, thereby improving the stability and efficiency of the battery. Studies have shown that this stacked structure can not only effectively improve the photoelectric conversion efficiency of the battery, but also achieve good performance in many experiments. However, although this method significantly optimizes battery performance in a short period of time, its preparation process still faces many challenges. First, the preparation process of the NiO nanoparticle layer is relatively complicated and requires multiple process steps, which increases the difficulty and cost of the overall preparation. Especially in actual production, this cumbersome process may lead to reduced production efficiency and difficulty in large-scale industrial application. Secondly, the preparation of the NiO nanoparticle layer usually requires a higher annealing temperature to ensure the stability and performance improvement of the material. This high-temperature annealing process not only increases energy consumption, but may also cause thermal damage to the materials of the perovskite active layer and other layers, thereby reducing the overall battery conversion efficiency. In addition, the NiO nanoparticle layer also has certain limitations in terms of photoelectric performance. The light transmittance of the pure NiO layer is relatively poor, which limits its application potential in high-efficiency perovskite solar cells. In addition, its photoelectric effect has not reached the ideal level, and it is unable to give full play to the advantages of perovskite materials, so the overall efficiency of the battery still has a lot of room for improvement.

[0004] More importantly, the NiO nanoparticle layer also has some problems in terms of environmental stability. Since NiO nanoparticle materials are easily reacted with moisture or oxygen when exposed to air, their performance will gradually degrade over time. This degradation not only affects the function of the NiO nanoparticle layer itself, but may also aggravate the interface degradation between the perovskite layer and the hole transport layer. In addition, the increase in oxygen vacancies on the NiO surface will further aggravate this interface degradation phenomenon, thereby affecting the long-term stability of the battery. This means that although the existing interface modification technology can improve the initial performance of perovskite cells to a certain extent, its long-term stability still has room for improvement. Therefore, although the existing technology has made some progress in optimizing the performance of perovskite solar cells, it still faces many challenges. Whether it is the degradation problem of the SAMs self-assembled molecular layer, or the process complexity, annealing temperature requirements and environmental stability of the NiO nanoparticle layer, these problems have limited the large-scale application and long-term stability of perovskite cells.

[0005] Therefore, how to provide a method for preparing a hole transport layer, a method for preparing a solar cell and a structure to improve the environmental stability of the hole transport layer, simplify the preparation process, reduce the annealing temperature requirements, and enhance the long-term stability, thereby improving the overall performance and long-term stability of the solar cell, has become an important technical problem that needs to be urgently solved by technical personnel in this field.

[0006] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application. Summary of the invention

[0007] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a method for preparing a hole transport layer, a method for preparing a solar cell and a structure thereof, so as to solve the problems existing in the prior art in terms of environmental stability, complexity of the preparation process, high annealing temperature requirements and long-term stability of the hole transport layer, as well as the problems affecting the overall performance and long-term stability of the solar cell.

[0008] To achieve the above object and other related objects, the present invention provides a method for preparing a hole transport layer, comprising the following steps:

[0009] Dissolving a self-assembling molecular material including a carbazole group and a phosphonic acid anchoring group in a first solvent to prepare a first solution;

[0010] Dissolving metal oxide nanoparticles in a second solvent to prepare a second solution;

[0011] According to a preset ratio, a certain amount of the first solution and the second solution are respectively extracted and mixed evenly to form a mixed solution, and the mixed solution is coated on a substrate and annealed to form a hole transport layer on the substrate.

[0012] Optionally, the self-assembling molecular material includes at least one of MeO-2PACz, 2PACz and Me-4PACz.

[0013] Optionally, the metal oxide nanoparticles include at least one of NiO nanoparticles, CuO nanoparticles, V2O5 nanoparticles, WO3 nanoparticles and ZnO nanoparticles.

[0014] Optionally, the concentration range of the self-assembling molecular material in the first solution is 0.1-5 mg / mL, the concentration range of the metal oxide nanoparticles in the second solution is 1-10 mg / mL, and the volume ratio of the first solution to the second solution is (1-10):1.

[0015] Optionally, the temperature range of the annealing treatment is 100-250° C., and the time range of the annealing treatment is 10-30 minutes.

[0016] To achieve the above object and other related objects, the present invention also provides a method for preparing a solar cell, comprising the following steps:

[0017] Providing a substrate and pre-treating the substrate;

[0018] Forming a hole transport layer on the substrate by using any one of the above methods for preparing a hole transport layer;

[0019] A perovskite precursor solution is prepared, the perovskite precursor solution is coated on the hole transport layer, the perovskite precursor solution is subjected to an anti-solvent treatment, and then an annealing treatment is performed to form a perovskite absorption layer on the hole transport layer;

[0020] forming an electron transport layer on the perovskite absorption layer;

[0021] A top electrode is formed on the electron transport layer.

[0022] Optionally, the general structural formula of the perovskite absorption layer material is ABX3, wherein A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge 2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.

[0023] Optionally, the substrate comprises transparent conductive glass or a silicon heterojunction bottom cell.

[0024] Optionally, the silicon heterojunction bottom cell includes a back transparent conductive layer, a P-type amorphous silicon layer, a second intrinsic amorphous silicon layer, an N-type silicon substrate layer, a first intrinsic amorphous silicon layer, an N-type amorphous silicon layer and an intermediate transparent conductive layer stacked in sequence from bottom to top, and the hole transport layer at least covers the intermediate transparent conductive layer.

[0025] Optionally, when the substrate is a silicon heterojunction bottom cell, the method further includes a step of forming a bottom electrode on a side of the back transparent conductive layer away from the middle transparent conductive layer.

[0026] Optionally, when the substrate is a silicon heterojunction bottom cell, the method further includes forming a front transparent conductive layer between the electron transport layer and the top electrode.

[0027] To achieve the above-mentioned purpose and other related purposes, the present invention also provides a solar cell structure, which includes a substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and a top electrode stacked in sequence, wherein the solar cell structure is obtained by any of the above-mentioned solar cell preparation methods.

[0028] As described above, the present invention provides a method for preparing a hole transport layer, a method for preparing a solar cell and a structure. The method forms a single-layer hole transport layer including self-assembled molecular materials and metal oxide nanoparticles by performing special process treatment on self-assembled molecular materials and metal oxide nanoparticles. This single-layer hole transport layer including both self-assembled molecular materials and metal oxide nanoparticles not only has a high light transmittance, but also can effectively improve the environmental stability of the materials in the hole transport layer, reduce the problem of degradation of self-assembled molecular materials and metal oxide nanoparticle materials caused by moisture and oxidation, and can also effectively simplify the preparation process of traditional multi-layer hole transport layers and reduce process complexity. In addition, while improving the transmission efficiency, the single-layer hole transport layer can also effectively promote the improvement of the crystallization quality of the perovskite absorption layer, making its crystallization more uniform and dense, thereby further improving the photoelectric conversion efficiency and long-term performance of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Shown is a process flow chart of the method for preparing the hole transport layer of the present invention.

[0030] Figure 2 It is a schematic diagram of the cross-sectional structure after forming the top electrode in the second embodiment of the preparation method of the solar cell of the present invention.

[0031] Figure 3 Shown is a photoluminescence (PL) spectrum of the perovskite absorption layer formed on the hole transport layer in a specific example of the preparation method of the solar cell of the present invention in Example 2, and a PL spectrum of the perovskite absorption layer formed on the hole transport layer of Comparative Example 1 compared with the specific example.

[0032] Figure 4 Shown is an X-ray diffraction (XRD) spectrum of the perovskite absorption layer formed on the hole transport layer in a specific example of the preparation method of the solar cell of the present invention in Example 2, and an XRD spectrum of the perovskite absorption layer formed on the hole transport layer of Comparative Example 1 compared with the specific example.

[0033] Figure 5 Shown are the UV-visible transmission spectra of the hole transport layer formed in a specific example of Example 2 of the preparation method of the solar cell of the present invention, and the UV-visible transmission spectra of the hole transport layer formed accordingly in Comparative Examples 1 and 2 compared with the specific example.

[0034] Figure 6 It is a schematic diagram of the cross-sectional structure after forming the bottom electrode in the third embodiment of the preparation method of the solar cell of the present invention.

[0035] Figure 7 It is a schematic diagram showing the results of a grazing incidence wide angle X-ray scattering (GIWAXS) test of the perovskite absorption layer formed on the hole transport layer in a specific example of the third embodiment of the method for preparing a solar cell of the present invention.

[0036] Figure 8 A schematic diagram showing the results of a grazing incidence wide-angle X-ray scattering (GIWAXS) test of a perovskite absorption layer formed on the hole transport layer of Comparative Example 3.

[0037] Component number description

[0038] 10 Base

[0039] 101 Silicon Heterojunction Bottom Cell

[0040] 11. Hole transport layer

[0041] 12 Perovskite absorber layer

[0042] 13 Electron transport layer

[0043] 14 Top electrode

[0044] 1011 N-type silicon substrate layer

[0045] 1012 first intrinsic amorphous silicon layer

[0046] 1013 N-type amorphous silicon layer

[0047] 1014 second intrinsic amorphous silicon layer

[0048] 1015 P-type amorphous silicon layer

[0049] 1016 Intermediate transparent conductive layer

[0050] 1017 Back transparent conductive layer

[0051] 15 Bottom electrode

[0052] 16 Front transparent conductive layer

[0053] Steps S1 to S3 DETAILED DESCRIPTION

[0054] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0055] See also Figures 1 to 8 It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0056] Embodiment 1

[0057] This embodiment provides a method for preparing a hole transport layer. Figure 1 , shown as a process flow chart of the method, comprising the following steps:

[0058] S1: dissolving a self-assembling molecular material including a carbazole group and a phosphonic acid anchoring group in a first solvent to prepare a first solution;

[0059] S2: dissolving the metal oxide nanoparticles in a second solvent to prepare a second solution;

[0060] S3: According to a preset ratio, a certain amount of the first solution and the second solution are respectively extracted and mixed evenly to form a mixed solution, and the mixed solution is coated on a substrate and annealed to form a hole transport layer on the substrate.

[0061] First, the step S1 is performed: dissolving the self-assembly molecular material including the carbazole group and the phosphonic acid anchoring group in a first solvent to prepare a first solution.

[0062] Specifically, a certain mass of the self-assembling molecular material is accurately weighed and placed in a clean and dry container (such as a test tube, beaker, centrifuge tube or conical flask, etc.), and then a predetermined volume of the first solvent is added. After that, the container is sealed and placed on a constant temperature shaker for oscillation at a constant temperature and a fixed speed. The oscillation time is controlled within 8 to 12 hours to ensure that the self-assembling molecular material is fully dissolved to form a uniform and stable first solution.

[0063] As an example, the self-assembling molecular material includes but is not limited to at least one of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) and (2,7-dimethoxy-9H-carbazole-9-yl)methylphosphonic acid (DC-PA).

[0064] As an example, the first solvent includes any one of methanol, ethanol and isopropanol.

[0065] Specifically, MeO-2PACz powder can be dissolved in ethanol to form the first solution, or 2PACz powder can be dissolved in isopropanol to form the first solution. When selecting the type of the self-assembling molecular material in the first solution and the specific type of the first solvent, it can be flexibly determined according to the needs of actual application, and is not specifically limited here.

[0066] As an example, the concentration range of the self-assembling molecular material in the first solution is 0.1-5 mg / mL.

[0067] Then, the step S2 is performed: dissolving the metal oxide nanoparticles in a second solvent to prepare a second solution.

[0068] Specifically, a certain mass of metal oxide nanoparticles is weighed and placed in a clean container (such as a test tube, beaker, centrifuge tube or conical flask, etc.), and when used, an appropriate amount of the second solvent is added, and the mixture is gently shaken (such as on a shaker) for 5-10 minutes until the metal oxide nanoparticles are fully dissolved to form the second solution. If necessary, the shaking time can be appropriately extended to ensure that the metal oxide nanoparticles are fully dissolved.

[0069] As an example, the metal oxide nanoparticles include at least one of nickel oxide (NiO) nanoparticles, copper oxide (CuO) nanoparticles, vanadium pentoxide (V2O5) nanoparticles, tungsten trioxide (WO3) nanoparticles, and zinc oxide (ZnO) nanoparticles.

[0070] As an example, the second solvent includes any one of deionized water, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), ethanolamine, and N-methylpyrrolidone (NMP).

[0071] As an example, the concentration of the metal oxide nanoparticles in the second solution is in the range of 1 to 10 mg / mL.

[0072] As an example, the second solution is prepared by a ready-to-use method.

[0073] Specifically, since the metal oxide nanoparticles have good solubility in the second solvent, the second solution is prepared in a ready-to-use manner without the need for advance preparation. In this embodiment, the first solution is formed in advance, and the second solution is prepared after the first solution is prepared. In this way, on the one hand, the stability and activity of the second solution can be guaranteed, and on the other hand, the risk of contamination of the second solution during storage can be effectively reduced, thereby ensuring the reliability of the solution quality during the experiment. It should be noted that the metal oxide nanoparticles can all show good solubility in the second solvent, and their solubility is not limited to a specific type of metal oxide nanoparticles or a type of second solvent. Therefore, the specific type of the metal oxide nanoparticles and the specific type of the second solvent can be flexibly selected and adjusted according to actual application requirements.

[0074] Then perform step S3: extract a certain amount of the first solution and the second solution respectively according to a preset ratio and mix them evenly to form a mixed solution, and apply the mixed solution on a substrate, and perform annealing treatment to form a hole transport layer on the substrate.

[0075] As an example, the volume ratio of the first solution to the second solution is (1-10): 1. More preferably, the volume ratio of the first solution to the second solution is (1-2):1.

[0076] As an example, the first solution and the second solution can be uniformly mixed by stirring, ultrasonic oscillation or other suitable methods. In this embodiment, the first solution and the second solution are preferably uniformly mixed by ultrasonic oscillation. During the ultrasonic oscillation process, the state of the mixed solution can be observed by the naked eye. When no large particle clusters or precipitation are seen, the oscillation operation can be stopped, thereby forming a uniform and stable mixed solution.

[0077] As an example, the ultrasonic oscillation time ranges from 20 to 40 minutes.

[0078] As an example, the temperature range of mixing the first solution and the second solution is 15-25°C.

[0079] Specifically, the method of coating the mixed solution on the substrate includes but is not limited to any one of spin coating, spray coating, drip coating, blade coating, roller coating, air knife coating and brush coating. In this embodiment, the mixed solution is preferably coated on the substrate by spin coating.

[0080] As an example, when the mixed solution is coated on the substrate by spin coating, the spin coating speed ranges from 1000 to 4000 rpm, and the spin coating time ranges from 20 to 60 seconds.

[0081] As an example, the temperature range of the annealing treatment is 100-250° C., and the time range of the annealing treatment is 10-30 minutes.

[0082] At this point, the hole transport layer is prepared.

[0083] The present embodiment provides a method for preparing a hole transport layer, by mixing a first solution with a self-assembled molecular material as a solute with a second solution with metal oxide nanoparticles as a solute to form a uniform mixed solution, and then forming a hole transport layer by coating and low-temperature annealing process. Compared with the traditional step-by-step preparation process, the method for preparing a hole transport layer in this embodiment simplifies the process flow, improves the preparation efficiency, has better adaptability, and can meet the needs of large-scale production. At the same time, the synergistic effect of the self-assembled molecular material and the metal oxide nanoparticles in the mixed solution can effectively overcome the problems that the traditional self-assembled molecular layer is prone to degradation, resulting in a weakened interface passivation effect, as well as the complex preparation process of metal oxide nanoparticles, high annealing temperature requirements, and poor environmental stability. The hole transport layer prepared in this embodiment can effectively resist the erosion of environmental factors such as moisture, oxygen or light, and has excellent environmental stability. In addition, the method for preparing the hole transport layer realizes annealing at a lower temperature, which can significantly reduce energy consumption and save energy costs.

[0084] Embodiment 2

[0085] This embodiment provides a method for preparing a solar cell, comprising the following steps:

[0086] (1) providing a substrate and pre-treating the substrate;

[0087] (2) forming a hole transport layer on the substrate by using any one of the hole transport layer preparation methods in Example 1;

[0088] (3) preparing a perovskite precursor solution, coating the perovskite precursor solution on the hole transport layer, performing an anti-solvent treatment on the perovskite precursor solution, and then performing an annealing treatment to form a perovskite absorption layer on the hole transport layer;

[0089] (4) forming an electron transport layer on the perovskite absorption layer;

[0090] (5) forming a top electrode on the electron transport layer.

[0091] Specifically, Figure 2As shown, step (1) is first performed: providing a substrate 10 and pre-treating the substrate 10.

[0092] As an example, the substrate 10 includes a transparent conductive glass or a silicon heterojunction bottom cell 101 .

[0093] In this embodiment, the substrate 10 is described by taking transparent conductive glass as an example.

[0094] As an example, the transparent conductive glass includes but is not limited to any one of indium tin oxide (ITO) glass, tungsten-doped indium oxide (IWO) glass, indium zinc oxide (IZO) glass, and fluorine-doped tin oxide (FTO) glass. In this embodiment, the transparent conductive glass is preferably ITO glass.

[0095] In one example, the process of pre-treating the substrate 10 includes: washing the substrate 10 with detergent, deionized water, acetone and isopropyl alcohol in sequence to remove organic or inorganic impurities on the surface of the substrate 10 .

[0096] In another example, the process of pre-treating the substrate 10 includes: washing the substrate 10 with anhydrous ethanol to remove organic or inorganic impurities on the surface of the substrate 10 .

[0097] As an example, after the pretreatment process of the substrate 10 is completed, the step of subjecting the substrate 10 to ultraviolet ozone irradiation treatment is also included.

[0098] Specifically, the substrate 10 is subjected to ultraviolet ozone irradiation treatment using ultraviolet ozone equipment, and the irradiation duration is 10 to 20 minutes, so as to further clean the substrate 10 .

[0099] Please perform step (2) again: adopt any one of the hole transport layer preparation methods in Example 1 to form a hole transport layer 11 on the substrate 10 .

[0100] As an example, the thickness of the hole transport layer 11 is in the range of 5 to 10 nanometers.

[0101] It should be noted that the substrate in Example 1 and the substrate 10 in this embodiment both refer to the support body as the basis for coating the hole transport layer. These supports not only have a simple supporting function, but can also flexibly realize other functions according to specific application requirements and designs. For example, in some application scenarios, the substrate 10 (or substrate) itself is part of the battery structure (such as transparent conductive glass, silicon heterojunction bottom battery). The process of forming a hole transport layer on the substrate described in Example 1 is equivalent to the process of forming a hole transport layer 11 on the substrate 10 in this embodiment.

[0102] Please then perform the step (3): prepare a perovskite precursor solution, apply the perovskite precursor solution on the hole transport layer 11, and perform anti-solvent treatment on the perovskite precursor solution, and then perform annealing treatment to form a perovskite absorption layer 12 on the hole transport layer 11.

[0103] As an example, the method of coating the perovskite precursor solution on the hole transport layer 11 includes but is not limited to any one of spin coating, spray coating, drop coating, blade coating, roller coating, air knife coating and brush coating. In this embodiment, the perovskite precursor solution is preferably coated on the hole transport layer 11 by spin coating.

[0104] As an example, when the perovskite precursor solution is coated on the hole transport layer 11 by spin coating, the spin coating speed ranges from 3000 to 5000 rpm, and the spin coating time ranges from 20 to 50 s.

[0105] Specifically, in this embodiment, an anti-solvent is added dropwise when there are 5 to 15 seconds of spin coating time remaining to perform anti-solvent treatment on the perovskite precursor solution.

[0106] As an example, the anti-solvent includes any one of chlorobenzene, ethyl acetate, anisole, dimethyl ethyl carbonate, ethanol and diethyl ether.

[0107] As an example, the temperature range of the annealing treatment performed after the anti-solvent treatment of the perovskite precursor solution is 80 to 130° C., and the time range of the annealing treatment is 10 to 20 minutes.

[0108] As an example, the general structural formula of the perovskite absorption layer 12 material is ABX3, where A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge 2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.

[0109] It should be noted that the specific composition of the perovskite absorption layer 12 material can be flexibly adjusted and optimized according to actual application requirements. For example, in a single-junction perovskite cell, by adjusting the types and proportions of A, B, and X-position ions, a wide-bandgap or narrow-bandgap perovskite absorption layer 12 can be prepared to meet different spectral response requirements. In perovskite / silicon heterojunction stacked solar cells, in order to maximize the overall light energy conversion efficiency, the bandwidth of the perovskite absorption layer 12 should be designed to be greater than the bandwidth of the silicon heterojunction cell, thereby ensuring that the perovskite absorption layer 12 can absorb and convert photon energy above the response range of the silicon layer.

[0110] As an example, the thickness of the perovskite absorption layer 12 is in the range of 400 to 600 nanometers.

[0111] Please perform step (4) again: forming an electron transport layer 13 on the perovskite absorption layer 12 .

[0112] As an example, the electron transport layer 13 is formed by any one of thermal evaporation, sputtering, spraying, spin coating and atomic layer deposition.

[0113] As an example, the electron transport layer 13 is fullerene (C 60 ) layer, tin dioxide (SnO2) layer, fullerene derivative (PCBM) layer and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) layer or at least two layers thereof, that is, the electron transport layer 13 is C 60 The single layer structure of the SnO2 layer, PCBM layer and BCP layer, or C 60 The stacked structure of two layers among the SnO2 layer, PCBM layer and BCP layer, or C 60 The stacked structure of three layers among the SnO2 layer, PCBM layer and BCP layer, or C 60 In this embodiment, the electron transport layer 13 preferably adopts C 60 A two-layer stacked structure consisting of a layer and a SnO2 layer, wherein the C 60 The thickness of the layer ranges from 10 to 30 nanometers, and the thickness of the SnO2 layer ranges from 20 to 30 nanometers.

[0114] Please perform step (5) again: forming a top electrode 14 on the electron transport layer 13 .

[0115] As an example, the top electrode 14 may be formed by, but not limited to, thermal evaporation, screen printing, magnetron sputtering, atomic layer deposition, chemical vapor deposition or other suitable methods. The material of the top electrode 14 includes, but is not limited to, any one of silver, copper, aluminum, nickel, chromium and gold. In this embodiment, the material of the top electrode 14 is preferably silver.

[0116] As an example, the thickness of the top electrode 14 is in the range of 100 to 400 nanometers.

[0117] Thus, a solar cell structure is prepared, and the solar cell structure is a single-junction inverted perovskite solar cell.

[0118] The method for preparing a solar cell provided in this embodiment successfully prepares a hole transport layer with high transparency and high stability by optimizing the formation method of the hole transport layer. The hole transport layer has multiple functions: on the one hand, it can effectively increase the transmittance of the incident light, so that more photons can enter the perovskite absorption layer, thereby significantly increasing the number of photogenerated carriers and increasing the photocurrent density; on the other hand, the hole transport layer has excellent environmental stability and can effectively resist the erosion of external environmental factors such as moisture, oxygen and light, thereby greatly improving the long-term stability of solar cells. In addition, the hole transport layer has a positive regulatory effect on the orderly growth of perovskite crystals, and can significantly improve the crystallization quality and interface characteristics of the perovskite absorption layer, so that the formed perovskite absorption layer has higher density and uniformity, thereby further improving the photoelectric conversion efficiency and long-term stability of solar cells.

[0119] The method for preparing the solar cell described in this embodiment is further introduced below in combination with a specific example, comparative example 1 and comparative example 2.

[0120] In a specific example, the method for preparing the solar cell includes the following steps:

[0121] (1) An ITO transparent conductive glass is provided, and the ITO transparent conductive glass is cleaned in sequence with detergent, deionized water, acetone and isopropyl alcohol, and the ITO transparent conductive glass after cleaning is placed in an isopropyl alcohol solution for storage. The ITO transparent conductive glass is then dried (dried with nitrogen) to ensure that the surface of the ITO transparent conductive glass is clean and free of liquid residue. Afterwards, the ITO transparent conductive glass is irradiated with ultraviolet ozone using an ultraviolet ozone device for 20 minutes to further clean the substrate 10.

[0122] (2) Accurately weigh a certain mass of MeO-2PACz powder, place it in a clean and dry container, add an appropriate amount of anhydrous ethanol and seal the container. Place the sealed container on a constant temperature shaker and oscillate it at a set room temperature and fixed speed for 8 to 12 hours (i.e., overnight treatment) to ensure that the MeO-2PACz powder is fully dissolved, thereby preparing the first solution. Then, weigh a certain mass of NiO nanoparticles, place it in a clean container, add an appropriate amount of deionized water, and gently oscillate on a shaker for 5-10 minutes to fully dissolve the NiO nanoparticles, thereby preparing the second solution, in which the dissolved concentration of the NiO nanoparticles in the second solution is 2 mg / mL. Thereafter, the first solution and the second solution are evenly mixed in a volume ratio of 1:1 to form the mixed solution. Finally, the mixed solution was spin-coated on the ITO transparent conductive glass at a spin-coating speed of 3000 rpm, and annealed at 200° C. for 10 minutes to form a hole transport layer 11 with a thickness of 5 nm.

[0123] (3) Methylammonium chloride (MACl), lead chloride (PbCl2), lead bromide (PbBr2), cesium iodide (CsI) and methylamine iodide (FAI) are dissolved in a mixed solvent consisting of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:3, and stirred until the mixture is uniform to form CsI. 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 perovskite precursor solution; 100uL of the Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 The perovskite precursor solution is spin-coated on the hole transport layer 11 at a rotation speed of 3000 rpm for 40 seconds, and an anti-solvent is added when the spin-coating time is 8 seconds. The anti-solvent can be ethyl acetate. Subsequently, an annealing treatment is performed at a temperature of 100° C. for 15 minutes to obtain the perovskite absorption layer 12 of 600 nanometers.

[0124] (4) Using thermal evaporation to form a C layer with a thickness of 10 nanometers on the perovskite absorption layer 12 60 The electron transport layer is then deposited by atomic layer deposition on the C 60 A SnO 2 electron transport layer with a thickness of 20 nanometers is formed on the electron transport layer to form the electron transport layer 13 .

[0125] (5) A silver top electrode 14 with a thickness of 130 nanometers is formed on the SnO2 electron transport layer by thermal evaporation to prepare the solar cell.

[0126] The preparation method of the solar cell in Comparative Example 1 is basically the same as the preparation method of the solar cell described in a specific example in this embodiment, the difference being that in Comparative Example 1, NiO nanoparticles are first dissolved in deionized water to form a first solution, and the first solution is applied on the ITO transparent conductive glass, and then annealed to form a NiO nanoparticle layer; thereafter, MeO-2PACz powder is dissolved in anhydrous ethanol to form a second solution, and the second solution is applied on the NiO nanoparticle layer, and annealed to form a MeO-2PACz layer, thereby obtaining a hole transport layer including a NiO nanoparticle layer and a MeO-2PACz layer. That is, the hole transport layer in Comparative Example 1 is formed by stacking the NiO nanoparticle layer and the MeO-2PACz layer.

[0127] The preparation method of the solar cell in Comparative Example 2 is basically the same as the preparation method of the solar cell described in a specific example in this embodiment, except that in Comparative Example 2, MeO-2PACz powder and NiO nanoparticles are added to an organic solvent (anhydrous ethanol) at the same time, and then stirred to form a dispersion. Then, the dispersion is coated on the ITO transparent conductive glass and annealed to form a hole transport layer. That is, the formation method of the solution in Comparative Example 2 is different from that in this example.

[0128] like Figure 3 As shown, the PL spectrum of the perovskite absorption layer formed on the hole transport layer in a specific example of the preparation method of the solar cell of the present invention in this embodiment, and the PL spectrum of the perovskite absorption layer formed on its hole transport layer in Comparative Example 1 compared with the specific example. It can be seen from the PL spectrum that the perovskite absorption layer 12 formed on the hole transport layer 11 in this example has a higher fluorescence intensity than that in Comparative Example 1, and its spectrum peak is slightly red-shifted. This shows that the preparation method of the hole transport layer described in this example helps to reduce the interface defects between the perovskite absorption layer and the hole transport layer, reduce non-radiative recombination, and thus improve the luminescence performance and the photoelectric conversion efficiency. In addition, the red shift phenomenon of the spectrum peak indicates that the internal stress of the perovskite absorption layer has been released or the crystal quality has been improved. This further shows that the preparation method of the hole transport layer in this example optimizes the growth environment of the perovskite crystal, can promote the growth of higher quality perovskite crystals, and thus enhance the interface charge transfer efficiency.

[0129] In addition, from Figure 4It can be seen from the XRD spectrum that the perovskite absorption layer 12 formed on the hole transport layer 11 in this example has more obvious crystal diffraction peaks than that in comparative example 1, especially (110), (220) and (310) crystal plane diffraction peaks. This shows that the perovskite absorption layer 12 formed on the hole transport layer 11 in this example has a significantly improved crystallinity. This optimized crystallization characteristic helps to reduce defects and non-radiative recombination at grain boundaries, thereby enhancing the mobility and diffusion length of carriers. In addition, the improvement in the crystallinity of the perovskite absorption layer 12 further shows that the preparation method of the hole transport layer in this example has a positive effect on the orderly growth of perovskite crystals, and can significantly improve the crystallization quality and interface characteristics of the perovskite absorption layer, thereby improving the film quality of the perovskite absorption layer 12, thereby significantly improving the performance stability and photoelectric conversion efficiency of solar cells.

[0130] In addition, from Figure 5 It can be seen from the UV-visible transmission spectrum that from the ultraviolet to near-infrared band range, the transmittance of the hole transport layer in this example is higher than that of Comparative Example 1 and Comparative Example 2 as a whole, especially in the visible light band in the range of 400 to 800 nanometers, its transmittance is much higher than that of Comparative Example 1, and in the ultraviolet band in the range of 340 to 430 nanometers, it is much higher than that of Comparative Example 2. This shows that the hole transport layer 11 material formed in this example has high light transmittance. And this high light transmittance helps more photons enter the perovskite absorption layer 12, thereby increasing the number of photogenerated carriers and improving the photocurrent density.

[0131] Embodiment 3

[0132] This embodiment provides a method for preparing a solar cell. The method for preparing a solar cell in this embodiment adopts basically the same technical solution as the method for preparing a solar cell in Embodiment 2, except that the substrate 10 in this embodiment is a silicon heterojunction bottom cell 101.

[0133] As an example, Figure 6 As shown, the silicon heterojunction bottom cell 101 includes a back transparent conductive layer 1017, a P-type amorphous silicon layer 1015, a second intrinsic amorphous silicon layer 1014, an N-type silicon substrate layer 1011, a first intrinsic amorphous silicon layer 1012, an N-type amorphous silicon layer 1013 and an intermediate transparent conductive layer 1016 stacked in sequence from bottom to top, and the hole transport layer 11 at least covers the intermediate transparent conductive layer 1016.

[0134] As an example, forming the silicon heterojunction bottom cell 101 includes the following steps:

[0135] (1) providing an N-type silicon substrate, and performing texturing and cleaning on the N-type silicon substrate to form a double-sided texturing N-type silicon substrate layer 1011;

[0136] (2) depositing a first intrinsic amorphous silicon layer 1012 and an N-type amorphous silicon layer 1013 on the front surface of the N-type silicon substrate layer 1011, and depositing a second intrinsic amorphous silicon layer 1014 and a P-type amorphous silicon layer 1015 on the back surface of the N-type silicon substrate layer 1011;

[0137] (3) forming an intermediate transparent conductive layer 1016 on the N-type amorphous silicon layer 1013;

[0138] (4) Forming a back transparent conductive layer 1017 on the P-type amorphous silicon layer 1015 .

[0139] Specifically, the N-type silicon substrate comprises an N-type single crystal silicon wafer, the thickness of the N-type silicon substrate is in the range of 150 to 200 microns, and the resistivity of the N-type silicon substrate is in the range of 1 to 10 Ω.cm.

[0140] Specifically, the N-type silicon substrate can be cleaned by KOH, NaOH solution or other suitable solution, and additives can be added to the KOH and NaOH solutions to control the size and uniformity of the velvet pyramids, so as to form a velvet structure on the opposite sides of the N-type silicon substrate, thereby forming a double-sided velvet N-type silicon substrate layer 1011. The temperature range of the velvet cleaning is 50 to 90°C, and the time range of the velvet cleaning is 5 to 20 minutes. The N-type silicon substrate layer 1011 formed in this embodiment can effectively reduce light reflection and improve light absorption efficiency.

[0141] Specifically, the first intrinsic amorphous silicon layer 1012, the N-type amorphous silicon layer 1013, the second intrinsic amorphous silicon layer 1014 and the P-type amorphous silicon layer 1015 may be formed by plasma enhanced chemical vapor deposition or other suitable methods. The first intrinsic amorphous silicon layer 1012 has a thickness ranging from 2 to 20 nanometers, the N-type amorphous silicon layer 1013 has a thickness ranging from 2 to 20 nanometers, the second intrinsic amorphous silicon layer 1014 has a thickness ranging from 2 to 20 nanometers, and the P-type amorphous silicon layer 1015 has a thickness ranging from 2 to 20 nanometers.

[0142] Specifically, the middle transparent conductive layer 1016 and the back transparent conductive layer 1017 are formed by magnetron sputtering, plasma enhanced chemical vapor deposition, thermal evaporation or other suitable methods. The material of the middle transparent conductive layer 1016 includes any one of ITO, IWO, IZO and FTO. In this embodiment, the middle transparent conductive layer 1016 is preferably an ITO layer, and the thickness of the middle transparent conductive layer 1016 is in the range of 50 to 200 nanometers. The material of the back transparent conductive layer 1017 includes any one of ITO, IWO, IZO and FTO, and the thickness of the back transparent conductive layer 1017 is in the range of 50 to 200 nanometers.

[0143] As an example, when the substrate 10 is a silicon heterojunction bottom cell 101 , the step of forming a bottom electrode 15 on a side of the back transparent conductive layer 1017 away from the middle transparent conductive layer 1016 is also included.

[0144] Specifically, the method of forming the bottom electrode 15 includes but is not limited to thermal evaporation, screen printing, magnetron sputtering, atomic layer deposition, chemical vapor deposition or other suitable methods.

[0145] Specifically, the material of the bottom electrode 15 includes but is not limited to any one of silver, copper, aluminum, nickel, chromium and gold.

[0146] Specifically, the thickness of the bottom electrode 15 is in the range of 80 to 250 nanometers.

[0147] As an example, when the substrate 10 is a silicon heterojunction bottom cell 101 , the step of forming a front transparent conductive layer 16 between the electron transport layer 13 and the top electrode 14 is also included.

[0148] Specifically, magnetron sputtering, plasma enhanced chemical vapor deposition, thermal evaporation or other suitable methods are used to form the front transparent conductive layer 16 on the electron transport layer 13. The material of the front transparent conductive layer 16 includes any one of ITO, IWO, IZO and FTO.

[0149] As an example, the thickness of the front transparent conductive layer 16 is in the range of 50 to 120 nanometers.

[0150] Thus, a solar cell structure is prepared, and the solar cell structure is a perovskite / silicon heterojunction stacked solar cell.

[0151] The present embodiment provides a method for preparing a solar cell, which achieves multi-faceted performance improvements by optimizing the formation method of the hole transport layer. On the one hand, the method forms a hole transport layer with high light transmittance and high stability. The hole transport layer not only has excellent performance itself, but also effectively promotes the orderly growth of crystals in the perovskite absorption layer, significantly improves the crystal orientation of the perovskite absorption layer crystals, and reduces grain boundary defects, thereby significantly reducing interface recombination losses and improving the overall performance of the battery. On the other hand, the method greatly improves the crystal quality and interface characteristics of the perovskite absorption layer, thereby enhancing the migration efficiency and diffusion capacity of carriers, and significantly suppresses the occurrence of non-radiative recombination, greatly improving the photoelectric conversion efficiency and long-term stability of solar cells.

[0152] The method for preparing the solar cell described in this embodiment is further introduced below in combination with a specific example and comparative example 3.

[0153] In a specific example, the method for preparing the solar cell includes the following steps:

[0154] (1) An N-type silicon substrate is provided, and the N-type silicon substrate is placed in a KOH solution at 70° C. for 10 minutes. A pyramid structure is formed on the front and back sides of the N-type silicon substrate by anisotropic etching of the N-type silicon substrate with an alkali solution, thereby obtaining the N-type silicon substrate layer 1011. Then, a first intrinsic amorphous silicon layer 1012 and a phosphorus-doped N-type amorphous silicon layer 1013 are sequentially deposited on the front side of the N-type silicon substrate layer 1011 by plasma enhanced chemical vapor deposition, and a second intrinsic amorphous silicon layer 1014 and a boron-doped P-type amorphous silicon layer 1015 are sequentially deposited on the back side of the N-type silicon substrate layer 1011. Afterwards, an ITO intermediate transparent conductive layer 1016 is formed on the N-type amorphous silicon layer 1013 by plasma enhanced chemical vapor deposition, and an ITO back transparent conductive layer 1017 is formed on the P-type amorphous silicon layer 1015, thereby obtaining the silicon heterojunction bottom cell 101.

[0155] (2) The silicon heterojunction bottom cell 101 is rinsed with anhydrous ethanol to remove organic or inorganic impurities on the surface of the silicon heterojunction bottom cell 101, and then the surface of the silicon heterojunction bottom cell 101 is blown dry with an air gun to ensure that the surface of the silicon heterojunction bottom cell 101 is clean and free of liquid residue. Finally, the silicon heterojunction bottom cell 101 is irradiated with ultraviolet ozone using an ultraviolet ozone device for 15 minutes to further clean the surface of the silicon heterojunction bottom cell 101.

[0156] (3) Accurately weigh a certain mass of MeO-2PACz powder, place it in a clean and dry container, add an appropriate amount of anhydrous ethanol and seal the container. Place the sealed container on a constant temperature shaker and oscillate it at a set room temperature and fixed speed for 8 to 12 hours to ensure that the MeO-2PACz powder is fully dissolved, thereby preparing the first solution, and the dissolved concentration of MeO-2PACz in the first solution is 1 mg / mL. Then, weigh a certain mass of NiO nanoparticles, place it in a clean container, add an appropriate amount of deionized water, and gently oscillate on a shaker for 5-10 minutes to fully dissolve the NiO nanoparticles, thereby preparing the second solution, and the dissolved concentration of the NiO nanoparticles in the second solution is 2 mg / mL. Afterwards, the first solution and the second solution were mixed evenly in a volume ratio of 1:1 to form the mixed solution, and the mixed solution was spin-coated on the surface of the silicon heterojunction bottom cell 101 at a spin-coating speed of 3000 rpm by spin coating, and the mixed solution covered the ITO intermediate transparent conductive layer 1016 and the surface of the N-type amorphous silicon layer 1013 not covered by the ITO intermediate transparent conductive layer 1016. Finally, an annealing treatment was performed at a temperature of 150° C. for 10 minutes to form a hole transport layer 11 with a thickness of 10 nanometers.

[0157] (4) dissolving methyl bromide (FABr), lead iodide (PbI2), CsI, FAI, cesium bromide (CsBr) and PbBr2 in a mixed solvent consisting of DMSO and DMF in a volume ratio of 1:3, and stirring until the mixture is uniform to form FABr. 0.8 Cs 0.2 PbI 1.95 Br 1.05 Perovskite precursor solution; the FA is prepared by a two-step method. 0.8 Cs 0.2 PbI 1.95 Br 1.05 The perovskite precursor solution was spin-coated on the hole transport layer 11. The first step was to spin-coat at a speed of 2000 rpm for 30 seconds, and the second step was to spin-coat at a speed of 5000 rpm for 20 seconds. At 10 seconds before the end of the spin coating, chlorobenzene was added dropwise for anti-solvent treatment. Subsequently, annealing was performed at a temperature of 100° C. for 15 minutes to obtain the perovskite absorption layer 12 with a thickness of 800 nanometers.

[0158] (5) Using thermal evaporation to form a C layer with a thickness of 10 nanometers on the perovskite absorption layer 12 60 The electron transport layer is then deposited by atomic layer deposition on the C 60 A SnO 2 electron transport layer with a thickness of 20 nanometers is formed on the electron transport layer to form the electron transport layer 13 .

[0159] (6) A 70-nanometer-thick IZO front transparent conductive layer 16 is sputtered on the SnO 2 electron transport layer by magnetron sputtering.

[0160] (7) A silver top electrode 14 with a thickness of 300 nanometers is formed on the IZO front transparent conductive layer 16 by thermal evaporation, and a silver bottom electrode 15 with a thickness of 200 nanometers is formed on the side of the ITO back transparent conductive layer 1017 away from the ITO middle transparent conductive layer 1016 by thermal evaporation to prepare the solar cell.

[0161] The preparation method of the solar cell in Comparative Example 3 is basically the same as the preparation method of the solar cell in a specific example of this embodiment, except that in Comparative Example 3, MeO-2PACz powder is dissolved in anhydrous ethanol to form a mixed solution, and then the mixed solution is coated on the surface of the silicon heterojunction bottom cell 101, and annealing is performed to form a MeO-2PACz layer. That is, in Comparative Example 3, the single-layer MeO-2PACz layer is used as the hole transport layer. Figure 7 and Figure 8 As shown, they are respectively a schematic diagram of the results of the GIWAXS test of the perovskite absorption layer formed on the hole transport layer in the above-mentioned specific example of the present invention, and a schematic diagram of the results of the GIWAXS test of the perovskite absorption layer formed on its hole transport layer in Comparative Example 3. It can be seen from the figure that the perovskite absorption layer 12 formed on the hole transport layer 11 in this example has a more ordered crystal arrangement and exhibits a higher diffraction intensity in different directions. The diffraction rings of Comparative Example 3 are more dispersed and the intensity is not concentrated, indicating that the crystal quality of its perovskite absorption layer is weak. This shows that the hole transport layer formed by the preparation method of the hole transport layer described in this example helps the perovskite absorption layer to have a higher degree of crystal orientation in the heterojunction structure, which helps to reduce interface recombination losses and improve battery performance.

[0162] Embodiment 4

[0163] The present embodiment provides a solar cell structure, which includes a substrate 10, a hole transport layer 11, a perovskite absorption layer 12, an electron transport layer 13 and a top electrode 14 stacked in sequence, wherein the solar cell structure is obtained by using any one of the solar cell preparation methods of Embodiment 2 and Embodiment 3.

[0164] In summary, the present invention provides a method for preparing a hole transport layer, a method for preparing a solar cell and a structure, wherein the method forms a single-layer hole transport layer comprising self-assembled molecular materials and metal oxide nanoparticles by performing special process treatment on self-assembled molecular materials and metal oxide nanoparticles. This single-layer hole transport layer comprising both self-assembled molecular materials and metal oxide nanoparticles not only has a high light transmittance, but also can effectively improve the environmental stability of the materials in the hole transport layer, reduce the problem of degradation of self-assembled molecular materials and metal oxide nanoparticle materials caused by moisture and oxidation, and can also effectively simplify the preparation process of the traditional multi-layer hole transport layer and reduce the process complexity. In addition, while improving the transmission efficiency, the single-layer hole transport layer can also effectively promote the improvement of the crystallization quality of the perovskite absorption layer, making its crystallization more uniform and dense, thereby further improving the photoelectric conversion efficiency and long-term performance of the solar cell. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.

[0165] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a hole transport layer, characterized in that: The following steps are involved: Dissolving a self-assembling molecular material including a carbazole group and a phosphonic acid anchoring group in a first solvent to prepare a first solution; Dissolving metal oxide nanoparticles in a second solvent to prepare a second solution; According to a preset ratio, a certain amount of the first solution and the second solution are respectively extracted and mixed evenly to form a mixed solution, and the mixed solution is coated on a substrate and annealed to form a hole transport layer on the substrate.

2. The method for preparing a hole transport layer according to claim 1, characterized in that: The self-assembling molecular material includes at least one of MeO-2PACz, 2PACz and Me-4PACz.

3. The method for preparing a hole transport layer according to claim 1, characterized in that: The metal oxide nanoparticles include at least one of NiO nanoparticles, CuO nanoparticles, V2O5 nanoparticles, WO3 nanoparticles and ZnO nanoparticles.

4. The method for preparing a hole transport layer according to claim 1, characterized in that: The concentration range of the self-assembling molecular material in the first solution is 0.1-5 mg / mL, the concentration range of the metal oxide nanoparticles in the second solution is 1-10 mg / mL, and the volume ratio of the first solution to the second solution is (1-10):

1.

5. The method for preparing a hole transport layer according to claim 1, characterized in that: The temperature range of the annealing treatment is 100-250° C., and the time range of the annealing treatment is 10-30 minutes.

6. A method for preparing a solar cell, characterized in that: The following steps are involved: Providing a substrate and pre-treating the substrate; Forming a hole transport layer on the substrate by using the method for preparing a hole transport layer according to any one of claims 1 to 5; A perovskite precursor solution is prepared, the perovskite precursor solution is coated on the hole transport layer, the perovskite precursor solution is subjected to an anti-solvent treatment, and then an annealing treatment is performed to form a perovskite absorption layer on the hole transport layer; forming an electron transport layer on the perovskite absorption layer; A top electrode is formed on the electron transport layer.

7. The method for preparing a solar cell according to claim 6, characterized in that: The general structural formula of the perovskite absorption layer material is ABX3, wherein A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge 2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.

8. The method for preparing a solar cell according to claim 6, characterized in that: The substrate includes transparent conductive glass or a silicon heterojunction bottom cell.

9. The method for preparing a solar cell according to claim 8, characterized in that: The silicon heterojunction bottom cell includes a back transparent conductive layer, a P-type amorphous silicon layer, a second intrinsic amorphous silicon layer, an N-type silicon substrate layer, a first intrinsic amorphous silicon layer, an N-type amorphous silicon layer and an intermediate transparent conductive layer stacked in sequence from bottom to top, and the hole transport layer at least covers the intermediate transparent conductive layer.

10. The method for preparing a solar cell according to claim 9, characterized in that: When the substrate is a silicon heterojunction bottom cell, the step further includes forming a bottom electrode on a side of the back transparent conductive layer away from the middle transparent conductive layer.

11. The method for preparing a solar cell according to claim 9, characterized in that: When the substrate is a silicon heterojunction bottom cell, the method further includes a step of forming a front transparent conductive layer between the electron transport layer and the top electrode.

12. A solar cell structure, characterized in that: The solar cell structure comprises a substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and a top electrode stacked in sequence, wherein the solar cell structure is obtained by the solar cell preparation method according to any one of claims 6 to 11.